Group Credit: Recent Evidence from the Philippines - Teodoro S. Untalan (Philippine Institute for Development Studies (PIDS), 1994)
This paper documents the interactions among borrowers that consist a group assuming joint liability. It describes the participants of group credit, their reasons for joining the group and the conditions why members are willing to assume other people's debt.
Keywords: 330; risk-taking; group credit; credit market; borrower; self-selection; free-riders; transaction costs